1992
DOI: 10.3109/02688699209002372
|View full text |Cite
|
Sign up to set email alerts
|

Outcome prediction in early management of severe head injury: An experience in Malaysia

Abstract: The outcome of 109 patients with severe head injury was studied in relation to clinical and computed tomographic (CT) criteria on admission, after resuscitation. Age, Glasgow Coma Score (GCS) and state of pupils strongly correlated with outcome. The presence of hypothalamic disturbances, hypoxia and hypotension were associated with an adverse outcome. The CT indicators associated with poor outcome were perimesencephalic cistern (PMC) obliteration, subarachnoid haemorrhage, diffuse axonal injury and acute subdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 16 publications
1
32
0
4
Order By: Relevance
“…No study has reported the prevalence in Africa. Only 2 of the 21 studies were from developing countries (7.33% from Kelantan, Malaysia and 0.68% from Rosario, Argentina) (Petroni et al, 2010;Selladurai et al, 1992) The overall prevalence in developing countries is 6.3%, which is higher than the overall prevalence of 2.8% in developed countries. The quality and availability of emergency and intensive care services differs among different regions.…”
Section: Locationmentioning
confidence: 80%
See 3 more Smart Citations
“…No study has reported the prevalence in Africa. Only 2 of the 21 studies were from developing countries (7.33% from Kelantan, Malaysia and 0.68% from Rosario, Argentina) (Petroni et al, 2010;Selladurai et al, 1992) The overall prevalence in developing countries is 6.3%, which is higher than the overall prevalence of 2.8% in developed countries. The quality and availability of emergency and intensive care services differs among different regions.…”
Section: Locationmentioning
confidence: 80%
“…After 2324 duplications removed, 1930 additional articles were excluded on the basis of their titles or abstracts, resulting in the full text of 341 articles being examined. Finally, 20 articles reporting 21 cohort studies were included in the present analysis (Andriessen et al, 2011;Fearnside, Cook, McDougall, & McNeil, 1993;Foulkes, Eisenberg, Jane, Marmarou, & Marshall, 1991;Gomez et al, 2000;Heiden, Small, Caton, Weiss, & Kurze, 1983;Jourdan et al, 2013;Judson, Cant, & Shaw, 1990;Lannoo et al, 2000;Mamelak, Pitts, & Damron, 1996;; L. S. Myburgh et al, 2008;Nordstrom, Messeter, Sundbarg, & Wahlander, 1989;Pang et al, 2007;Petroni et al, 2010;Rusnak, Janciak, Majdan, Wilbacher, & Mauritz, 2007;Selladurai, Jayakumar, Tan, & Low, 1992;Stranjalis et al, 2008;Turazzi, Bricolo, & Pasut, 1984;Turazzi, Bricolo, Pasut, & Formenton, 1987). A flow diagram of the selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vários estudos têm examinado a associação entre a TC de crânio, a gravidade da lesão e o prognóstico (Gennarelli et al, 1982;Greene et al, 1995;Kido et al, 1992;Wardlaw et al, 2002 (Gennarelli et al, 1982;Eisenberg et al, 1990;Selladurai et al, 1992;Kakarieka et al, 1994;Greene et al, 1995;Greene et al, 1996;Chesnut et al, 2000;Ono et al, 2001;Servadei et al, 2002 (Annegers et al, 1980); em San Diego as maiores taxas foram constatadas na faixa etária de 16 a 25 anos (Kraus et al, 1984) e no Bronx, o pico de incidência foi verificado na faixa etária de 16 a 30 anos (Cooper et al, 1983 ( Durkin et al, 1998). No entanto, em um estudo científico realizado em Minnesota entre 1965 a 1972, incluindo todos os casos de TCE, de todas as faixas etárias, foi detectado que 15% dos casos encontrava-se na faixa etária de 0 a 1 ano, 17% na de 2 a 10 anos e 26% na faixa etária de 11 a 20 anos (Annegers et al, 1980 (Jager et al, 2000) e de 1,5:1 no período de 1995 a 1996 (Guerrero et al, 2000).…”
Section: Introductionunclassified